Panic symptoms in transient loss of consciousness: Frequency and diagnostic value in psychogenic nonepileptic seizures, epilepsy and syncope. (May 2017) - Rawlings, G.H.; Jamnadas-Khoda, J.; Broadhurst, M.; Grünewald, R.A.; Howell, S.J.; Koepp, M.; Parry, S.W.; Sisodiya, S.M.; Walker, M.C.; Reuber, M.
Highlights: Patients with epilepsy, PNES or syncope can report ictal panic. Ictal panic is more common in patients with PNES than epilepsy or syncope. Ictal panic symptoms are infrequent in most patients with PNES. Ictal panic can help to differentiate between PNES and epilepsy or syncope. Self-report questionnaires may have implications for diagnosis and treatment. Abstract: Purpose: Previous studies suggest that ictal panic symptoms are common in patients with psychogenic nonepileptic seizures (PNES). This study investigates the frequency of panic symptoms in PNES and if panic symptoms, just before or during episodes, can help distinguish PNES from the other common causes of transient loss of consciousness (TLOC), syncope and epilepsy. Methods: Patients with secure diagnoses of PNES (n = 98), epilepsy (n = 95) and syncope (n = 100) were identified using clinical databases from three United Kingdom hospitals. Patients self-reported the frequency with which they experienced seven symptoms of panic disorder in association with their episodes. A composite panic symptom score was calculated on the basis of the frequency of symptoms. Results: 8.2% of patients with PNES reported "never" experiencing any of the seven panic symptoms in their episodes of TLOC. Patients with PNES reported more frequent panic symptoms in their attacks than those with epilepsy (p < 0.001) or syncope (p < 0.001), however, patients with PNES were more likely "rarely" or "never" to report five of the seven-ictal panic symptoms than "frequently" or "always" (45–69% versus 13–29%). A receiver operating characteristic analysis demonstrated that the composite panic symptom score distinguished patients with PNES from the other groups (sensitivity 71.1%, specificity 71.2%), but not epilepsy from syncope. Conclusions: Patients with PNES report TLOC associated panic symptoms more commonly than those with epilepsy or syncope. Although panic symptoms are reported infrequently by most patients with PNES, a composite symptom score may contribute to the differentiation between PNES and the other two common causes of TLOC.